Patterns in (in)directness: An exploratory case study in the external history of Portuguese translations of Polish literature (1855–2010) - Pięta, Hanna (2017)
The goal of this descriptive, exploratory paper is to identify and analyse patterns in a case study of direct and indirect literary transfer from Poland to Portugal between 1855 and 2010. By doing so, the paper intends to contribute to a deeper understanding of indirect translation. Firstly, relevant information concerning the corpus is presented. Secondly, the methodological issues are elucidated. Thirdly, the results of the study are discussed in detail. More specifically, the correlations between the dependent variables (directness and indirectness) and the independent variables (author profile, translator profile, publisher profile and target text literary genre) are examined. In addition, the correlation between the occurrence of the label ‘(in)direct’ is tested against the independent time variable. Finally, the preliminary conclusions and future research avenues are presented.